Peritoneal tuberculosis: case report (Brazilian Journal of Health Research, 2025)
Introduction: Tuberculosis is an infectious, transmissible disease caused by the bacillus Mycobacterium tuberculosis, with the lungs being the most affected organ. Abdominal tuberculosis is the sixth most affected extrapulmonary site, affecting the gastrointestinal tract, peritoneum or mesenteric lymph nodes. Peritoneal tuberculosis affects both sexes and is related to low socioeconomic status, crowding and is associated with other comorbidities. It is an insidious disease. The main signs and symptoms are abdominal pain, ascites, weight loss and fever. Objective: To report a case of peritoneal tuberculosis, a rare and sometimes underdiagnosed disease, to assist health professionals in early diagnosis and treatment. Case report: A 60-year-old man, hypertensive and ex-smoker for 8 days, presented with diffuse abdominal pain and increased abdominal volume. Abdominal physical examination revealed mobile dullness. Diagnostic paracentesis revealed hypercellular ascitic fluid with a predominance of mononuclear cells, with a serum-ascites albumin gradient
Keywords: Peritoneal tuberculosis; Mycobacterium tuberculosis; Ascites; Laparoscopy